An evaluation of graduate teaching education programs in Region XII - Mantawil, Maniaga P. 1934-
Graduate teacher education programs were favorably rated in terms of instructional systems, administration systems, physical plant and facilities, policies and standards, and human resources. The graduates of the masters degree program were professionally competent and performed satisfactorily on the job. Multiple stepwise regression analysis showed that sex and monthly salary of masters graduates influence their professional competence and job performance. Age influence competence but not performance. Civil status and years after completion of masters degree were not related to competence or performance.